Practical PowerPivot & DAX formulas for Excel 2010 - Tennick, Art (McGraw-Hill Education, 2010)
This solutions-based guide contains more than 200 DAX queries that can be immediately applied across a wide variety of BI-related problems. It begins with fundamental principles and simple queries and rapidly progresses to complex and sophisticated queries.